1998
DOI: 10.1121/1.424374
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a toroidal bend on wind instrument tuning

Abstract: In a toroidal bend in a cylindrical wind instrument, with the same cross section as the cylindrical part, the inertance for longitudinal waves is reduced. This induces a change in the resonance frequency. The magnitude of this change depends on the length and the sharpness of the bend and on its position in the sound field. A transition to a cylinder gives an additional inertance correction. The present study compares known results from literature and adds new facts, employing analytical and numerical methods.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…c o m / l oc a t e / a p a c o u s t where p is the pressure, x is the angular frequency, q is the medium density, / is the curvature angle, and R is the distance from the point to the curvature center. Nederveen [7] assumed the radial dependence of the pressure is small at low frequency which meant the pressure is the same over the cross section; this is valid for the frequency range discussed in this paper. Therefore, the particle velocity is:…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 86%
“…c o m / l oc a t e / a p a c o u s t where p is the pressure, x is the angular frequency, q is the medium density, / is the curvature angle, and R is the distance from the point to the curvature center. Nederveen [7] assumed the radial dependence of the pressure is small at low frequency which meant the pressure is the same over the cross section; this is valid for the frequency range discussed in this paper. Therefore, the particle velocity is:…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 86%
“…Several authors attempted to quantify the effect of the curvature on the tuning. Nederveen 2,3 and later Keefe and Benade 4 showed that in a bent duct, in the long wavelength limit, the inertance is lowered relative to its value in a straight duct having the same cross-section. The curvature induces an increase in resonance frequencies.…”
Section: Introductionmentioning
confidence: 97%
“…Morse and Ingard 8 along with Sundberg et al 9 assumed that acoustic propagation at low frequencies follows a wave mode characterized by the conformal grid characteristic of streamline flow: 10 the wavefronts are defined by curved lines of constant-pressure in two dimensions ͑2Ds͒, curved surfaces in three dimensions ͑3Ds͒, that intersect the vocal-tract walls at right angles. 8,9,11,12 The flow in an acoustic wave is a local back-and-forth disturbance, not a bulk streaming flow, but it is assumed for the stated conditions that the acoustic particle velocities are aligned with streamlines under steady potential flow. Pressure measurements of cast models of the vocal tract 13 along with a finite-element model 14 ͑FEM͒ confirm those assumptions for frequencies up to 4 kHz for the shapes studied, although another FEM study showed a departure from such a plane-wave propagation mode at 1.5 kHz in the case of the large front cavity for /r/.…”
Section: Introductionmentioning
confidence: 99%